Molecular Analysis of Cytochrome Oxidase I in Bemisia tabaci (Gennadius) Populations Collected from Four Districts in the Special Region of Yogyakarta - Ayuningtias, Nandini; Witjaksono, Witjaksono; Wijonarko, Arman; Soffan, Alan (Universitas Gadjah Mada, 2022)
Bemisia tabaci is an agricultural pest that interferes plant growth, as well as being an insect vector of various types of viruses, one of which is the geminivirus group. B. tabaci is called Cryptic Species Complex due to their similar morphology but has different genetic profiles. Climate change and increased global trading of agricultural products could increase B. tabaci population and lead to the emergence of genetic disparity. This study aims to obtain the latest information on the population homogeneity of B. tabaci in four districts of the Yogyakarta and potential differences on their nucleotide arrangements. Molecular identification was performed using PCR and primers C1-J-2198/L2-N-3914 on B. tabaci. B. tabaci COI gene sequences were then compared using a phylogenetic analysis and similarities of nucleotide bases were determined. Results showed that the populations of B. tabaci in Yogyakarta were still homogeneous showed by biotypes similarity, namely the non-B biotype. B. tabaci from Yogyakarta have nucleotide base similarity of 100% with B. tabaci from Singapore (AY686095) and Thailand (AY686092) and 99.56% with species from Bangladesh (AJ748388). Results also showed no differences in the composition of both nucleotide bases and amino acids from the four districts of B. tabaci sampling location. The homogeneous population of B. tabaci and the high incidence of yellowing disease caused by Begomovirus in chili pepper plants in the Special Region of Yogyakarta prove that it is necessary to review the current methods of controlling B. tabaci pests.